Accuracy of implant impression using a multifunctional guide in the all-on-four treatment concept - Vasconcelos, Juliano de Alencar [UNESP]; Castanharo, Sabrina Maria [UNESP]; Aroni, Monica Estefania Tinajero [UNESP]; Araújo, Raphael Ferreira de Souza Bezerra [UNESP]; Rigolin, Maria Silvia Mauricio [UNESP]; Oliveira, Lucas Portela [UNESP]; Mollo Júnior, Francisco de Assis [UNESP] (My University, 2020)
Introduction: The passivity of prosthetic components is one of the most important prerequisites in oral implant rehabilitation for maintenance of osseointegration. Objective: Thus, the present study analyzed in vitro the accuracy of different molding techniques in prosthetic rehabilitation on angled implants installed in an anatomical model of a metallic edentulous maxilla. Methods: Laboratory experiment study. A reference metal model of an edentulous maxilla was used. A metal framework was used for the misadaptation assessment. Three groups (n= 10) were compared and impressions were made with vinylpolysiloxane and casts were obtained with type IV stone: (1) Impression with a metallic open-tray without splinted transfers; (2) Impression with a metallic open-tray and metal splinted transfers; (3) Impression with a multifunctional guide and metal splinted transfers. Misadaptation was assessed with the aid of a stereomicroscope and measuring software. Data were submitted to ANOVA with Welch correction and the Games-Howell post-hoc test with the significance set at 5 %. Results: Misadaptation (µm) was 110,23 ± 30,94, 37,53 ± 3,92, and 37,69 ± 2,79 for the the groups. Statistically significant differences between impression with a metallic open-tray with and without splinted transfers were observed (p < 0,001). No significant differences between the other types of impression. Conclusions: Impression with a metallic open-tray without splinted transfers and with a multifunctional guide splinted with metal transfers were the most precise methods resulting in higher accuracy in transferred implants.
Evaluación de la precisión de impresiones sobre implantes usando guía multifuncional en el sistema all-on-four
Keywords: Dental implants; Dental impression materials; Dental impression technique; Dental materials